Penerapan Terapi Musik untuk Menurunkan Kecemasan pada Pasien yang Akan Dilakukan Percutaneous Coronary Intervention (PCI) - Tallulembang, Abdi; Jumaiyah, Wati; Yunitri, Ninik; Arsianti, Lyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This his study aims to overcome anxiety in CHD patients who will undergo percutaneous coronary intervention (PCI). The method used was random sampling with a sample of 12 CHD patients who were going to undergo PCI. This sample size was obtained from calculations using G-Power version 3.1.9.4. The research results showed that the characteristics of the participants in the EBNP were an average age of 48.4 years (12.3%), male 9 (75.0%), Muslim 7 (58.4%), high school education 5 (41.7%), married status 11 (91.7%), BPJS health insurance for retired military personnel 5 (41.7). The results of the T-Test analysis or comparison test of state anxiety inventory and trait anxiety inventory before and after being given music therapy showed a P value of 0.000. In conclusion, music therapy has a significant effect on reducing anxiety in patients with coronary heart disease who will undergo PCI or percutaneous coronary intervention. Keywords: Anxiety, CHD, Music therapy